2016
DOI: 10.1021/acs.est.6b01686
|View full text |Cite
|
Sign up to set email alerts
|

Soil Weathering as an Engine for Manganese Contamination of Well Water

Abstract: Manganese (Mn) contamination of well water is recognized as an environmental health concern. In the southeastern Piedmont region of the United States, well water Mn concentrations can be >2 orders of magnitude above health limits, but the specific sources and causes of elevated Mn in groundwater are generally unknown. Here, using field, laboratory, spectroscopic, and geospatial analyses, we propose that natural pedogenetic and hydrogeochemical processes couple to export Mn from the near-surface to fractured-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Concentrations of these contaminants and co-ions are governed by groundwater-sediment interactions, involving the primary mineral phase of concern and secondary processes. For instance, dissolution of calcite has been identified to release coprecipitated F, As, Ba, U, and Sr at some locations. , Also, dissolution of evaporite minerals is known to affect pH and alkalinity of groundwater, which were found to induce mobilization of contaminants from primary host minerals (e.g., desorption of U from U-bearing minerals). , Furthermore, among the prevalent co-ions in groundwater high dissolved Mn is often taken as a proxy for the presence of Mn oxide-rich phases, which are known to favorably adsorb dissolved U­(VI) . Controlled lab experiments have shown that under oxic conditions high dissolved Mn may even promote U­(IV) mineral dissolution through the formation of a redox couple between the short-lived Mn­(III) and U­(VI), , where dissolved Mn­(II) converts to Mn­(III) after consuming dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of these contaminants and co-ions are governed by groundwater-sediment interactions, involving the primary mineral phase of concern and secondary processes. For instance, dissolution of calcite has been identified to release coprecipitated F, As, Ba, U, and Sr at some locations. , Also, dissolution of evaporite minerals is known to affect pH and alkalinity of groundwater, which were found to induce mobilization of contaminants from primary host minerals (e.g., desorption of U from U-bearing minerals). , Furthermore, among the prevalent co-ions in groundwater high dissolved Mn is often taken as a proxy for the presence of Mn oxide-rich phases, which are known to favorably adsorb dissolved U­(VI) . Controlled lab experiments have shown that under oxic conditions high dissolved Mn may even promote U­(IV) mineral dissolution through the formation of a redox couple between the short-lived Mn­(III) and U­(VI), , where dissolved Mn­(II) converts to Mn­(III) after consuming dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Metals such as cobalt (Co), copper (Cu), manganese (Mn), and zinc (Zn) are beneficial to live beings because they participate in vital processes in their bodies, but in high quantities, they become toxic and contaminate the environment . The presence of manganese in high concentrations in aquatic environments, usually from industrial processes such as mining and ore processing, causes inorganic pollution due to the fact that the metal is not biodegradable, presents toxicity and can accumulate in humans and animals, causing adverse reactions . Therefore, the removal of such metals from polluted water has attracted considerable attention .…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation is that close to the water table, there may be more solid-phase manganese oxides to catalyze Cr oxidation, which has been widely recognized as an important pathway for Cr oxidation. Gillispie et al 65 showed that chemically reactive Mn oxides accumulate near the water table in the weathered saprolite in the North Carolina Piedmont. Cr oxidation catalyzed by Mn oxides could explain the higher Cr(VI) concentration in this zone, and especially the well with orders of magnitude higher Cr(VI) than any other monitoring well, including other wells in the same cluster and aquifer lithology.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%